2018
DOI: 10.17219/acem/68634
|View full text |Cite
|
Sign up to set email alerts
|

F2-isoprostanes and F4-neuroprostanes as markers of intracranial aneurysm development

Abstract: Background. Intracranial aneurysms are common, occurring in about 1-2% of the population. Saccular aneurysm is a pouch-like pathological dilatation of an intracranial artery that develops when the cerebral artery wall becomes too weak to resist hemodynamic pressure and distends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The same lipid oxidation susceptibility could affect the male reproductive traits and, in particular, the semen quality of animals feeding on n-3 PUFAs, considering that dietary source influences the PUFA profile of sperm (see Section 2.3). In agreement, recent studies (reviewed by [126]) demonstrated that lipid membrane peroxidation generates a series of molecules, namely isoprostanes, which are retained “markers of oxidation” in many male infertility-related pathologies [127] or neurodegenerative disease (i.e., Rett syndrome or Alzheimer’s disease [128]). Isoprostanes are prostaglandin-like products, which are formed via nonenzymatic, free radical-mediated peroxidation of polyunsaturated fatty acids, for example, the oxidation of arachidonic acid (n-6 LC-PUFA) produces F2-isoprostanes (F2-IsoPs), whereas the oxidation of EPA and DHA (n-3 LC-PUFAs) produces F3-isoprostanes (F3-IsoPs) and F4-neuroprostanes (F4-NeuroPs), respectively [129].…”
Section: Different Effects Of N-3 Pufasmentioning
confidence: 53%
“…The same lipid oxidation susceptibility could affect the male reproductive traits and, in particular, the semen quality of animals feeding on n-3 PUFAs, considering that dietary source influences the PUFA profile of sperm (see Section 2.3). In agreement, recent studies (reviewed by [126]) demonstrated that lipid membrane peroxidation generates a series of molecules, namely isoprostanes, which are retained “markers of oxidation” in many male infertility-related pathologies [127] or neurodegenerative disease (i.e., Rett syndrome or Alzheimer’s disease [128]). Isoprostanes are prostaglandin-like products, which are formed via nonenzymatic, free radical-mediated peroxidation of polyunsaturated fatty acids, for example, the oxidation of arachidonic acid (n-6 LC-PUFA) produces F2-isoprostanes (F2-IsoPs), whereas the oxidation of EPA and DHA (n-3 LC-PUFAs) produces F3-isoprostanes (F3-IsoPs) and F4-neuroprostanes (F4-NeuroPs), respectively [129].…”
Section: Different Effects Of N-3 Pufasmentioning
confidence: 53%
“…An alternative to the formation of reactive aldehydes is the intramolecular cyclization of lipid hydroperoxides. This causes the formation of prostaglandin derivatives, including isoprostanes (mainly from arachidonic acid) and neuroprostanes (mainly from docosahexaenoic acid), which are characterized by the presence of a cyclopentane ring [79,80]. Cyclic derivatives increase the production of ROS in mitochondria and further disturb the redox balance by oxidizing endogenous antioxidants, in particular, GSH [80].…”
Section: Ros-dependent Lipid Peroxidation Productsmentioning
confidence: 99%
“…Syta-Krzyzanowska et al [62] showed that in cerebral tissues, where the level of DHA is high (similarly to testes), a pathological situation (e.g., aneurysm) leads to the enhancement of lipid peroxidation with an increase in plasma F 2 -IsoPs and F 4 -NeuroPs (more than three-fold and eleven-fold, respectively). Related work [63] suggested that the metabolism of LC PUFA yields oxidised bioactive compounds that 9 Oxidative Medicine and Cellular Longevity mediate its effects.…”
mentioning
confidence: 99%